Micro Estimation of Some Hydrazine Derivatives with Bromamine-T - Shukla, I.C.; Rai, O.P. (Asian Journal of Chemistry, 2010)
A simple, convenient and a method of choice has been developed for the micro estimation of some hydrazine derivatives. Milligram amount (1–5 mg) of the sample is allowed to react with excess of bromamine-T in 2N-sulphuric acid medium at room temp. for 10–15 minutes. After the reaction is over, the unconsumed reagent is back titrated iodometrically. The accuracy of the method is within ± 1 %.